Anemia Awareness and Iron Supplement Adherence Among Adolescent Girls in East Kalimantan - Sumiati, Sumiati; Halipah, Nur; Meihartati, Tuti; Abiyoga, Aries (Poltekkes Kemenkes Surakarta, 2026)
Background: Anemia remains a prevalent health issue among adolescent girls, often resulting from menstrual blood loss and insufficient iron intake. Globally, anemia prevalence among adolescents ranges from 40 to 88%. In Indonesia, the rate is 32%, while in East Kalimantan it reaches 43.2%. At Senior High School 3 Penajam Paser Utara, 57.14% of female students were identified as anemic. This condition may impair health, reduce learning concentration, and increase the risk of pregnancy complications in later life. This study aimed to analyze the association between anemia awareness and adherence to iron supplement consumption among adolescent girls at Senior High School 3 Penajam Paser Utara, East Kalimantan Methods: A cross-sectional study with a descriptive-analytic design was employed, involving 74 adolescent girls through simple random sampling. Data were collected using the Morisky Medication Adherence Scale (MMAS) questionnaire, and statistical analysis was performed with the Chi-square test. Results: Among the 74 respondents, 53 (71.6%) demonstrated low awareness of anemia, and 55 (74.3%) were non-adherent to iron supplement consumption. The Chi-square test revealed a significant association between anemia awareness and adherence (p = 0.001 p < 0.05). Conclusion: Adolescent girls with higher awareness of anemia were more likely to adhere to iron supplement consumption compared to those with lower awareness.